Internationalization Strategies, Entry Modes and Cultural Dimensions of Chinese Way of Doing Business in Europe - FIKADU TOLOSSA AYANIE (Universitas Muhammadiyah Yogyakarta, 2018)
Abstract This paper presents the process of Chinese outward direct investment in Europe. A remarkable feature of the Chinese cross-border business expansion is the essential role of government in the internationalization of Chinese MNCs which was supported by official policy instruments, including the famous “go global” strategy that encouraged thousands of Chinese firms to invest abroad. It argues that the driving motive of Chinese firms to go abroad aimed at acquiring new skills, advanced technology, brands and supply chains that would enhance their competitive advantage in international as well as domestic markets. To this end, the Chinese investment in Europe has generally targeted few but major economies, namely Germany, UK and France. Merger and acquisitions has been the leading market entry mode resulting in huge takeovers characterizing Chinese investment in Europe. It is also apparent that the internationalization process of Chinese business companies did not follow the traditional Uppsala model as psychic distance and experiential knowledge didn’t play a role. Nevertheless, it is evident that the path-dependency of Chinese expatriates in European countries has made it difficult to learn and adapt to the local work environment that exhibits diverging and contrasting cultural values. This huge cross-cultural gap, often portrayed in the literature as “culture conflict”, constitutes the biggest challenge that Chinese companies face, in their international operations in general, and could undermine their effectiveness in doing business in European countries in particular.